2016
DOI: 10.4172/2315-7844.1000187
|View full text |Cite
|
Sign up to set email alerts
|

Managers Approaches on the Intention to Retain Older Employees in the Corporate Sectors in Libya

Abstract: This study aim to achieve a better thoughtful of the Executives' disposition to explore the factors that influence the intention to Retain Older Employees in Corporate Sectors in Libya using Theory of paling behavior as a model. However, the study analyzed the intention of managers to absorb older employees in an organization through pragmatic behaviors and engagements. As a result, the study engaged the theory of planned behavior (TPB). It focused on the unwelcome stereotype attitude meted out to the older em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(70 reference statements)
0
0
1
Order By: Relevance
“…However, the result contradicts the findings of Ruël et al (2007), and Parry (2011), which concluded that there was a negative relationship. HRM promotes organizational performance while reducing costs (Dhar et al, 2017;Salah, 2018;Salah & Habtoor, 2017). Strategic effectiveness is associated with teamwork, HR skill development, effective communication, and the alignment of strategic orientation to HRM policies and organizational business strategy.…”
Section: Resultscontrasting
confidence: 86%
“…However, the result contradicts the findings of Ruël et al (2007), and Parry (2011), which concluded that there was a negative relationship. HRM promotes organizational performance while reducing costs (Dhar et al, 2017;Salah, 2018;Salah & Habtoor, 2017). Strategic effectiveness is associated with teamwork, HR skill development, effective communication, and the alignment of strategic orientation to HRM policies and organizational business strategy.…”
Section: Resultscontrasting
confidence: 86%